2020
DOI: 10.1155/2020/7351214
|View full text |Cite
|
Sign up to set email alerts
|

Framingham Risk Stratification of Middle-Aged Migraineurs

Abstract: Introduction. Migraine is a common primary headache disorder involving about 10-15% of the whole population. Several epidemiological and prospective studies showed a link between migraine (especially migraine with aura) and cardio- and cerebrovascular events. Objectives. We prospectively analyzed the data of vascular event-free middle-aged patients with migraine who were referred to our Headache Clinic between 01/2014 and 01/2018. Framingham 10-year risk were calculated; covariates included in the analysis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Prior studies on the relationship between vascular risk, as operationalized by the FRS or by one of its vascular risk factor components, and migraine status have shown conflicting results. Although some studies reported increased FRS among those with migraine, 28,29 another study reported a decreased risk in the hypertension component of the FRS among those with migraine compared with those without migraine. 30 Yet other studies reported increased risk of developing hypertension among women with migraine.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies on the relationship between vascular risk, as operationalized by the FRS or by one of its vascular risk factor components, and migraine status have shown conflicting results. Although some studies reported increased FRS among those with migraine, 28,29 another study reported a decreased risk in the hypertension component of the FRS among those with migraine compared with those without migraine. 30 Yet other studies reported increased risk of developing hypertension among women with migraine.…”
Section: Discussionmentioning
confidence: 98%
“…Epidemiological and clinical considerations demonstrate that obesity increases morbidity in migraine and headache, whereas weight loss can improve headache morbidity [ 70 ]. The association between migraine and dyslipidemia has been observed in case-control [ 71 ] and population studies [ 72 ].…”
Section: Discussionmentioning
confidence: 99%